2023
DOI: 10.1111/pbi.14024
|View full text |Cite
|
Sign up to set email alerts
|

A novel R2R3‐MYB transcription factor FaMYB5 positively regulates anthocyanin and proanthocyanidin biosynthesis in cultivated strawberries (Fragaria × ananassa)

Abstract: Flavonoids have a major contribution to the fruit quality in cultivated strawberries and are regulated by MYB, bHLH and WD40 transcriptional factors. We reported here the identification of the FaMYB5, an R2R3-MYB transcription factor, which positively regulated the accumulation of anthocyanins and proanthocyanidins through the trans-activation of the F3'H and LAR. The strawberry FaEGL3 and FaLWD1/FaLWD1-like interact with the R2R3-FaMYB5 to form an MYB-bHLH-WD40 complex (MBW), enhancing the regulatory efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 76 publications
(129 reference statements)
3
42
0
Order By: Relevance
“…As previously reported, R2R3-FaMYB5 had an intact R2 domain compared with the former investigated R3-FaMYB5, another start codon can be found at 83 aa before R3-FaMYB5, which could encode an MYB5 protein with a complete R2R3 domain ( Figures 1A, B ; Schaart et al., 2013 ; Jiang et al., 2023 ). Sequence alignment results indicated that FaMYB1, R2R3-FaMYB5, FaMYB9, FaMYB10, and FaMYB11 belong to R2R3-type MYB TFs, in which FaMYB1 had an EAR repression motif (pdLNLD/EL) of flavonoids on the C2 domain ( Figure 1A ; Aharoni et al., 2001 ).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…As previously reported, R2R3-FaMYB5 had an intact R2 domain compared with the former investigated R3-FaMYB5, another start codon can be found at 83 aa before R3-FaMYB5, which could encode an MYB5 protein with a complete R2R3 domain ( Figures 1A, B ; Schaart et al., 2013 ; Jiang et al., 2023 ). Sequence alignment results indicated that FaMYB1, R2R3-FaMYB5, FaMYB9, FaMYB10, and FaMYB11 belong to R2R3-type MYB TFs, in which FaMYB1 had an EAR repression motif (pdLNLD/EL) of flavonoids on the C2 domain ( Figure 1A ; Aharoni et al., 2001 ).…”
Section: Resultssupporting
confidence: 71%
“…In our previous report ( Jiang et al., 2023 ), it was preliminarily elucidated the interaction between FaMYB5, FaEGL3, FaLWD1 and FaLWD1-like proteins. Here, we expanded the test gene list to get the full landscape of the MBW complex in strawberry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 The MBW ternary complex, which is essential in regulating the expression of genes related to anthocyanin synthesis, comprises a MYB, a bHLH, and a WD40 TF. 13,14 For example, R2R3-MYBs in the MBW recognize and bind to target gene promoters, directly affecting anthocyanin accumulation by determining the expression levels and tissue specificity of downstream structural genes. 15,16 In addition, two distinct groups of MYB TFs, the CPC-MYB (R3-MYB) 17−19 and R2R3-MYB repressors, 20,21 also play significant roles in the regulatory network controlling anthocyanin biosynthesis.…”
Section: ■ Introductionmentioning
confidence: 99%